2011
DOI: 10.1007/s10508-011-9780-y
|View full text |Cite
|
Sign up to set email alerts
|

Doing More Good than Harm? The Effects of Participation in Sex Research on Young People in the Netherlands

Abstract: Ethical guidelines for research with human participants stress the importance of minimizing risks and maximizing benefits. In order to assist Institutional Review Boards (IRBs) and researchers to make more informed risk/benefit analyses with regard to sex research among adolescents, the current study examined the effects of participation in sex research among 899 young people (15-25 years old). Participants completed three questionnaires on a wide range of sexuality-related measures. They also completed scales… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
62
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 37 publications
8
62
0
1
Order By: Relevance
“…This concern was typically framed in terms of the child's being too immature to assent to participation, with some limited elaboration provided about specific reservations linked to the child's developmental readiness or the presence of some form of intellectual disability (Szollos and McCabe 1995;Wilson et al 2010). While some children may truly be vulnerable and in need of parental oversight, the data about negative consequences of participation in adolescent sexuality research suggest that such concerns are unfounded, even for youth with mild learning disabilities (Halpern et al 1994;Kuyper et al 2012;Thomas and Kroese 2005). Other forms of risk were alluded to with less frequency.…”
Section: Parental Reasons For Granting or Denying Consent For Adolescmentioning
confidence: 99%
“…This concern was typically framed in terms of the child's being too immature to assent to participation, with some limited elaboration provided about specific reservations linked to the child's developmental readiness or the presence of some form of intellectual disability (Szollos and McCabe 1995;Wilson et al 2010). While some children may truly be vulnerable and in need of parental oversight, the data about negative consequences of participation in adolescent sexuality research suggest that such concerns are unfounded, even for youth with mild learning disabilities (Halpern et al 1994;Kuyper et al 2012;Thomas and Kroese 2005). Other forms of risk were alluded to with less frequency.…”
Section: Parental Reasons For Granting or Denying Consent For Adolescmentioning
confidence: 99%
“…Malpass, et al (2015) for example use the term 'symbolic violence' (Bourdieu, 1996) There is a concern that contributing to DVA research is associated with increased risk of violence if the perpetrators come to know about it. However, it has been suggested that this concern to some extent has been based in assumptions, anecdotal evidence (Griffin, Resick, Waldrop, & Mechanic, 2003;Kuyper, de Wit, Adam, & Woertman, 2012) or "…worst case scenarios of research atrocities" (Sikweyiya & Jewkes, 2012, p. 1). On the contrary, such participation can be beneficial and cathartic (Edwards, Kearns, Calhoun, & Gidycz, 2009;Sikweyiya & Jewkes, 2012) and may prove empowering (Downes, Kelly, & Westmarland, 2014).…”
Section: Participant's Safetymentioning
confidence: 99%
“…Nakon početnoga vala, anketiranje je ponovljeno nakon 6, 12, 18 i 24 mjeseca, pri čemu u ovome radu rabimo isključivo podatke iz početnoga (T0), drugoga (T1) te četvrtoga vala (T2). Kao u sličnom nizozemskom istraživanju (Kuyper, De Wit, Adam i Woertman, 2012), između prvoga i drugoga vala odaziv sudionika smanjio se za više od dvije trećine, nakon čega se stabilizirao.…”
Section: Metoda Uzorakunclassified